MEDIA MONITORING PROCEDURES AS A PUBLIC RELATIONS TOOL IN THE WEST JAVA PROVINCIAL HOUSE OF REPRESENTATIVES: TATA LAKSANA MEDIA MONITORING SEBAGAI INSTRUMEN KEHUMASAN DI DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI JAWA BARAT - Ahmad Anwar Ripa'i; Saifullah Zakaria; Jovanscha Qisty Adinda (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
Digital transformation demands that government public relations be adaptive in managing the flow of information through media monitoring activities. This study analyzes the media monitoring procedures in the West Java Provincial Council (DPRD), which are deemed suboptimal due to their manual operation and the absence of technical regulations. Using George C. Edwards III's Policy Implementation Theory approach, this qualitative descriptive study uncovered an implementation paradox. Key findings indicate that implementers' dispositions are very positive, with a strong work ethic. However, their effectiveness is hampered by a weak bureaucratic structure resulting from the absence of Standard Operating Procedures (SOPs). This results in a lack of clarity in the communication of instructions and resource inefficiencies due to slow, manual work methods. This study concludes that formalizing procedures through the development of SOPs and digital transformation are absolutely necessary to transform the media monitoring function from an administrative routine into a strategic intelligence instrument for DPRD leaders